Moving the Research Forward: The Best of British Biology Using the Tractable Model System Dictyostelium discoideum - Robin S. B. Williams (MDPI AG, 2021)
The social amoeba Dictyostelium discoideum provides an excellent model for research across a broad range of disciplines within biology. The organism diverged from the plant, yeast, fungi and animal kingdoms around 1 billion years ago but retains common aspects found in these kingdoms. Dictyostelium has a low level of genetic complexity and provides a range of molecular, cellular, biochemical and developmental biology experimental techniques, enabling multidisciplinary studies to be carried out in a wide range of areas, leading to research breakthroughs. Numerous laboratories within the United Kingdom employ Dictyostelium as their core research model. This review introduces Dictyostelium and then highlights research from several leading British research laboratories, covering their distinct areas of research, the benefits of using the model, and the breakthroughs that have arisen due to the use of Dictyostelium as a tractable model system.